2020
DOI: 10.1111/jbi.14018
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting a speciation classic: Comparative analyses support sharp but leaky transitions betweenBombinatoads

Abstract: Aim-The amount of gene flow between parapatric species can be greatly variable depending on how species boundaries are maintained in respect to numerous genetic and ecological factors that affect the strength of reproductive isolation. We quantified this variability to understand its effect on the genetic integrity of a well-studied pair of hybridizing amphibians. Location-Central and Eastern Europe Taxa-The fire-and yellow-bellied toads Bombina bombina and B. variegata. Methods-We first complemented the mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Even between mostly incompatible genomes, some neutral loci are expected to diffuse far within species ranges once recombination has broken down linkage between them and the barrier loci (Barton 1979, Polechová & Barton 2011). Accordingly, speciation is often achieved before interspecies gene flow entirely stops, so sharp clines may be paralleled by far-ranging introgression without questioning the taxonomic status of lineages (as shown in Bombina toads, Dufresnes et al 2021b). However, the potential unreliability of the outlier clines reported here and the use of diagnostic loci only prevents the interpretation of the genomic landscape of introgression.…”
Section: Discussionmentioning
confidence: 99%
“…Even between mostly incompatible genomes, some neutral loci are expected to diffuse far within species ranges once recombination has broken down linkage between them and the barrier loci (Barton 1979, Polechová & Barton 2011). Accordingly, speciation is often achieved before interspecies gene flow entirely stops, so sharp clines may be paralleled by far-ranging introgression without questioning the taxonomic status of lineages (as shown in Bombina toads, Dufresnes et al 2021b). However, the potential unreliability of the outlier clines reported here and the use of diagnostic loci only prevents the interpretation of the genomic landscape of introgression.…”
Section: Discussionmentioning
confidence: 99%
“…First, given the limited opportunity for sampling we cannot rule out that clines in the south were missed, just as we would not have encountered some displaced clines if the northern leg of the transect had been short. Second, we are forced to rely on a single transect whereas several studies on multiple transects across the same hybrid zone revealed different patterns of introgression, governed by a variety of demographic and environmental parameters (Dufresnes et al, 2021; Harrison & Larson, 2016; Janoušek et al, 2012; Szymura & Barton, 1986, 1991; Teeter et al, 2010). Further analysis of additional transects (if these were to exist) and extending the sampling of the southern populations could help to test and refine our inferences.…”
Section: Discussionmentioning
confidence: 99%
“…We compiled laboratory details (DNA yields and sequencing success) of 771 samples initially processed in genomic studies of Bombina (Dufresnes et al, 2021a), Hyla (Dufresnes et al, 2019a), Pelobates (Dufresnes et al, 2019b), Pelophylax (Dubey et al, 2019), Alytes (Dufresnes and Martinez-Solano, 2020a), Pelodytes and Discoglossus (Dufresnes et al, 2020b), and compared the performance of buccal swabs, tail clipping of tadpoles, toe clipping of adults, muscle tissue obtained from fixed specimens, and road kills.…”
Section: Methodsmentioning
confidence: 99%